Analisis Unjuk Kerja Four Stroke Diesel Engine Menggunakan Bahan Bakar Multi-Feesdstock Biodiesel Menggunakan (Minyak Kelapa Sawit, Minyak Kelapa, Minyak Jagung) - Sugiantoro .; Muhammad Shah; Edi Haryono (Proceedings Conference on Marine Engineering and its Application, 2023)
The massive increase in the world's population has led to an increase in fuel consumptionin the world. The most popular energy still relies on fossil fuels today, which are depleting the earth'sreserves, so an alternative fuel is needed, namely biodiesel. Biodiesel has the advantages of beingbiodegradable, non-poisonous, has low emissions, and is renewable in availability. The biologicalmaterials that can be used as biodiesel are palm oil, coconut oil, and corn oil. In this research, thethree feedstocks were blended into a composition (multi-feedstock biodiesel) which was mixed withHSD (Pertamina dex) to become B20, B35 and B100 fuels. The fuels were tested on a four-strokediesel engine with 1000 watts, 2000 watts and 3000 watts lamp loading with engine speed variationsfrom 900 rpm to 1050 rpm. From the test results, it was found that the performance results in theform of power, torque, and generator-specific fuel consumption values were the most optimal, namelyB100 fuel. From this research, the most optimal percentage of fuel mixture is 100% multi-feedstockbiodiesel or pure biodiesel.